GAMBARAN KADAR HEMOGLOBIN IBU HAMIL DI PUSKESMAS NANIA KOTA AMBON - Fasiha Fasiha (Jurnal Kebidanan, 2023)
Blood hemoglobin (Hb) is a parameter used to determine the prevalence of anemia. The increased plasma volume causes the hemoglobin concentration to decrease somewhat during pregnancy. As a result, the overall viscosity of the blood is reduced. The normal Hb value at the end of pregnancy averages 12.5 g/dL, and about 5% of pregnant women have an Hb level of less than 11.0 g/dL. The purpose of this study was to find out the description of hemoglobin levels in pregnant women at the Nania Health Center. The method used is a type of descriptive research, the number of respondents is 34 people obtained by random sampling. Hemoglobin levels were measured with a Sahli Hemoglobinometer. The results showed that 7 respondents (21%) had low hemoglobin levels and 27 respondents (79%) had normal hemoglobin levels. In this study, it was also found that mothers with low Hb were caused by their disobedience in taking fe tablets.